The influence of the preparation methods on the inclusion of model drugs in a beta-cyclodextrin cavity - Salustio, P. J. (2015)
The work aims to prove the complexation of two model drugs (ibuprofen, IB and indomethacin, IN) by beta-cyclodextrin (beta CD), and the effect of water in such a process, and makes a comparison of their complexation yields. Two methods were considered: kneading of a binary mixture of the drug, beta CD, and inclusion of either IB or IN in aqueous solutions of beta CD. In the latter method water was removed by air stream, spray-drying and freeze-drying. To prove the formation of complexes in final products, optical microscopy, UV spectroscopy, IR spectroscopy, DSC, X-ray and NMR were considered. Each powder was added to an acidic solution (pH = 2) to quantify the concentration of the drug inside beta CD cavity. Other media (pH = 5 anti 7) were used to prove the existence of drug not complexed in each powder, as the drugs Solubility increases with the pH. It was observed that complexation occurred in all powders, and that the fraction of drug inside the beta CD did not depend neither oil the method of complexation nor on the processes of drying considered. (C) 2008 Elsevier B.V. All rights reserved.